Multi-chemokine receptor antagonist RAP-103 inhibits opioid-derived respiratory depression, reduces opioid reinforcement and physical dependence, and normalizes opioid-induced dysregulation of mesolimbic chemokine receptors in rats. (1st September 2022) - Bongiovanni, Angela R.; Zhao, Pingwei; Inan, Saadet; Wiah, Sonita; Shekarabi, Aryan; Farkas, Daniel J.; Watson, Mia N.; Wimmer, Mathieu E.; Ruff, Michael R.; Rawls, Scott M.
Abstract: Chemokine-opioid crosstalk is a physiological crossroads for influencing therapeutic and adverse effects of opioids. Activation of chemokine receptors, especially CCR2, CCR5 and CXCR4, reduces opioid-induced analgesia by desensitizing OPRM1 receptors. Chemokine receptor antagonists (CRAs) enhance opioid analgesia, but knowledge about how CRAs impact adverse opioid effects remains limited. We examined effects of RAP-103, a multi-CRA orally active peptide analog of "DAPTA", on opioid-derived dependence, reinforcement, and respiratory depression in male rats and on changes in chemokine and OPRM1 (µ opioid) receptor levels in mesolimbic substrates during opioid abstinence. In rats exposed to chronic morphine (75 mg pellet x 7 d), daily RAP-103 (1 mg/kg, IP) treatment reduced the severity of naloxone-precipitated withdrawal responses. For self-administration (SA) studies, RAP-103 (1 mg/kg, IP) reduced heroin acquisition (0.1 mg/kg/inf) and reinforcing efficacy (assessed by motivation on a progressive-ratio reinforcement schedule) but did not impact sucrose intake. RAP-103 (1–3 mg/kg, IP) also normalized the deficits in oxygen saturation and enhancement of respiratory rate caused by morphine (5 mg/kg, SC) exposure. Abstinence from chronic morphine elicited brain-region specific changes in chemokine receptor protein levels. CCR2 and CXCR4 were increased in the ventral tegmental area (VTA), whereas CCR2 and CCR5 were reduced in the nucleus accumbens (NAC). Effects of RAP-103 (1 mg/kg, IP) were focused in the NAC, where it normalized morphine-induced deficits in CCR2 and CCR5. These results identify CRAs as potential biphasic function opioid signaling modulators to enhance opioid analgesia and inhibit opioid-derived dependence and respiratory depression. Highlights: Effects of multi-chemokine receptor antagonist RAP-103 were investigated. RAP-103 reduced heroin acquisition and reinforcing efficacy. RAP-103 reduced development of morphine physical dependence. RAP-103 inhibited morphine-derived respiratory depression. RAP-103 normalized chemokine receptor dysregulation during morphine abstinence.